Paragomphus sofiae sp. nov.—a new spotted species of Hooktail from Madagascar (Odonata: Anisoptera: Gomphidae) - Bernard, Rafał; Daraż, Bogusław (Zootaxa, 2026)
Paragomphus Cowley, 1934 is a large palaeotropical dragonfly genus with four species previously described from Madagascar. The species identity of three of them requires confirmation, and only Paragomphus fritillarius (Selys, 1892) did not raise any taxonomical doubts. In this paper, a new species, Paragomphus sofiae sp. nov. from the Sofia River basin in lowlands of northern Madagascar, is described and compared to superficially very similar P. fritillarius. Identification of both species was possible only by comparing their hamules with the type specimens of P. fritillarius in the Selys’ collection, because the literature contained neither illustrations nor detailed descriptions of its secondary genitalia. Regardless of the great similarity in the colour pattern, these species have turned out to be well-defined and differ by their notably distinct hamules and caudal appendages. They also seem to be spatially and ecologically separated: although both inhabit clearwater and sandy watercourses, P. sofiae has been recorded in open large, braided rivers so far and P. fritillarius in smaller rivers and streams. Considering the new knowledge of confusing interspecies similarity and species-specific hamules and cerci, all previous records of P. fritillarius require confirmation; the discovery of further species from the fritillarius-group is potentially possible.